9-5z=12-(z+7)

Simple and best practice solution for 9-5z=12-(z+7) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 9-5z=12-(z+7) equation:


Simplifying
9 + -5z = 12 + -1(z + 7)

Reorder the terms:
9 + -5z = 12 + -1(7 + z)
9 + -5z = 12 + (7 * -1 + z * -1)
9 + -5z = 12 + (-7 + -1z)

Combine like terms: 12 + -7 = 5
9 + -5z = 5 + -1z

Solving
9 + -5z = 5 + -1z

Solving for variable 'z'.

Move all terms containing z to the left, all other terms to the right.

Add 'z' to each side of the equation.
9 + -5z + z = 5 + -1z + z

Combine like terms: -5z + z = -4z
9 + -4z = 5 + -1z + z

Combine like terms: -1z + z = 0
9 + -4z = 5 + 0
9 + -4z = 5

Add '-9' to each side of the equation.
9 + -9 + -4z = 5 + -9

Combine like terms: 9 + -9 = 0
0 + -4z = 5 + -9
-4z = 5 + -9

Combine like terms: 5 + -9 = -4
-4z = -4

Divide each side by '-4'.
z = 1

Simplifying
z = 1

See similar equations:

| 8y+11=6y+11 | | 11-13/15x=209 | | 7(x-7)+4x=-2(x+5) | | 3(12+10)=36x-8 | | x-.25x=30 | | 11x+4=11x-9 | | 6-x=4x-9 | | 1.5x+4.1=-2.8 | | 12+2x=p | | -14.5=-0.2+2.6 | | 6x^3=7x-1 | | 20x-5x+5=0 | | 7(2x+7)=14x+49 | | -8k^2-3k-4=0 | | -6=2+5x-6x | | 4(a-7)=-44 | | 2n+7=4n+8 | | -2(3x+5)=6-19x | | 2(x^2-5)(x-2)=0 | | 0=(0.3t^2)-6t+30 | | 9-m=3.5 | | -3(4s-6)-18=-2(9s+3)-3 | | 5(h-3)+2h+12= | | (y-5)(110)= | | X+140.00=0.05x | | 7=-5p+4p | | x^2+6x+5=2y-18 | | -1=-x+2 | | logy=5x+6 | | 6x+15=69x-30 | | 3x+19=-2x | | 4x-6x=7x-9+4x |

Equations solver categories